Напівформальні правила - Абрамов, Федір Володимирович (НТУ "ХПІ", 2016)
У статті розглядаються причини виникнення та основні риси напівформальних правил. Показано, що напівформальні правила мають такі ж самі риси, що й формальні правила, за виключенням їх документальної фіксації. Аналізується вплив напівформальних правил на ефективність чинних формальних правил. Показано, що існує три головні фактори стабільності напівформальних правил: високий рівень дискреційних повноважень керівництва установи, брак прийнятних альтернатив для працевлаштування та високий рівень трансакційних витрат бюрократичних процедур. Пропонуються заходи попередження виникнення напівформальних правил.

This paper deals with the phenomenon of semi-formal rules. It is shown that apart from formal and informal rules, institutional environment includes semi-formal rules. The reasons for appearance of semi-formal rules are given. The paper presents the main features of semi-formal rules. The paper argues that the semi-formal rules have the same main features as formal rules, except that they are not externally materialized in written. There are two main reasons why semi-formal rules are not externally materialized in written. The first is that the semi-formal rules contradict written legal sets of rules. The second is that the semi-formal rules could contradict the public interest. The impact of semi-formal rules on the efficiency of formal rules is analysed. The analysis suggests that the semi-formal rules is one of the causes of inefficiency of formal rules. The study finds that there are three main determinants of stability of semi-formal rules: the extreme degree of discretionary power of the managers in public sector, especially if there is enough room for discretionary interpretation of collective bargaining agreements, the lack of acceptable job opportunities for government employees, the high level of transaction costs of bureaucratic procedures. The ways for restriction of semi-formal rules in public sector are given. Our results prove that the moust efficient tool for restriction of semi-formal rules in public sector is the sharp reduction in the level of transaction costs of bureaucratic procedures.
Semi-formal rules
Keywords: правила формальні; правила неформальні; витрати трансакційні; процедури бюрократичні; фактори сталості; formal rules; informal rules; transaction costs; bureaucratic procedures; determinants of stability